Successful control of invasive crayfish ( Pacifastacus leniusculus) by intensive trapping in a small lake - Ruokonen, Timo; Erkamo, Esa; Tulonen, Jouni; Hämäläinen, Heikki (Regional Euro-Asian Biological Invasions Centre, 2025)
Despite strict regulations, invasive alien species (IAS) pose an increasing threat to native ecosystems. In aquatic environments, difficulties in early detection of invasions make it challenging to control the spread of species such as freshwater crayfish, and hence, effective measures are often needed to eradicate already established populations. We investigated the efficacy of intensive trapping in eradication of signal crayfish (Pacifastacus leniusculus) from a small, isolated lake using a Before-After-ControlImpact (BACI) design with data from three control lakes. Five years of intensive biannual removal of crayfish catch in the target lake resulted in a collapse of the crayfish population, in contrast to increasing test catches in the control lakes. A temporary recovery of the population followed within four years after stopping the removal, but a short-term continuation of the intensive trapping reduced the population to apparent extinction. While small crayfish (< 60 mm in total length) were not effectively caught by the size selective traps, the trial apparently succeeded in limiting the adult crayfish and their reproduction below a critical threshold. Our results support the previous findings that complete direct removal of individuals may not be necessary for successful eradication. Climate-induced reproductive failure and low availability of suitable habitat likely supported our eradication success, highlighting the importance of environmental conditions in invasive species management. Our results emphasise the need for removal projects to be well targeted, long-term, and adequately resourced. Less selective traps catching also small crayfish would need to be developed for enhancing the invasive crayfish species management.
Keywords: BACI; eradication; management of invasive species; signal crayfish